Development of Self-Potential in Pondok Education Curriculum - Khairul Nizam bin Zainal Badri (Pascasarjana IAIN Sultan Amai Gorontalo, 2022)
The establishment of pondok studies in the Malay world is in line with the existence of Malay-Islamic kingdoms. Since then, the pondok school has become an educational platform for the Malay community. The uniqueness of pondok studies is that the education system stands according to the Malay-Islamic mold without neglecting the importance of the Arabic language in its curriculum. Thus, many study texts written in Jawi are produced to meet the demands and needs of the local community. In addition to imparting knowledge, the pondok school also plays a role in developing students' skills. This is where the motivation to conduct research, to find out the role and contribution played by the pondok school from the point of view of developing human potential. The methodology used is document analysis which refers to the writings related to the study of the pondok. Overall, the qualitative method was chosen because it is more relevant for the purposes of collection, screening, analysis and drawing conclusions on the data taken from the document. The study found that pondok study centers offer highly effective study and life routines for skills growth, although the facilities available at the pondok are unlikely to match the facilities provided at full boarding schools or universities.